Unique truncated and non-synonymous mutations in functional domains of ORF3a SARS-CoV-2 - Jeanne Elvia Christian; Hartiyowidi Yuliawuri (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2023)
Previous studies showed that mutations in the SARS-CoV-2 ORF3a protein can influence viral pathogenesis. Therefore, it is necessary to observe mutations, especially in the functional domain of the protein. We observed the presence of mutations in the ORF3a protein by analyzing 5,131 samples from the GISAID database since it was first discovered in March 2020 until November 2021. The sequence was aligned using Clustal Omega Multiple Sequence Alignment from EMBL-EBI and analyzed using BioEdit version 7.2.5 software using reference sequences NC045512. Samples having the letter N were omitted from the analysis. The effect of point mutations on proteins was analyzed using the Protein Variation Effect Analyzer (PROVEAN) v1.1.3 software. The functional domains of the ORF3a protein were visualized using RasWin software. We identified 312 mutations in the SARS-CoV-2 ORF3a protein. In addition, from 5,131 samples, 915 samples were found to be truncated in the C-terminal region of the protein. These non-synonymous mutations data in functional domains and truncated sequences indicate that amino acid changes in the ORF3a protein require further studies to determine the effect of viral pathogenicity in humans.